(untitled) (Discourse of Law and Administration, 2025)
A short report from the 1st Constitutional Conference entitled "Restitution of the rule of law in the Republic of Poland" organized on December 12, 2023 at the SWPS University in Warsaw by the local Constitutional Law Science Club in cooperation with the SWPS Institute of Law. The event, consisting of three one-hour panels, covered the following areas: (1) "Restitution of the rule of law in courts and the Constitutional Court", (2) the National Council of the Judiciary, in particular the issue of "(...) restoring the legality and verification of judges appointed in the years 2018 - 2023", and (3) "Restoring culture of law and good parliamentary customs in the bodies of the legislative power".